An Educational Intervention to Increase Health Literacy Levels of Faculty of Health Sciences Students (Turkey Health Literacy Journal, 2021)
Purpose: In this study, it is aimed to increase the level of health literacy of the students who are studying at the Faculty of Health Sciences and who will take place in different stages of health service provision in the future with educational intervention. Method: This study is an intervention study. Students of Ankara Gazi University Faculty of Health Sciences were given a 12-week face-to-face training within the sope of 2019-2020 Fall Period Health Literacy course. Pre and post-training health literacy levels were measured with Turkey Health Literacy Scale-32. The data were analyzed with the SPSS 23 program. Pre-test and post-test scores were compared using the Wilcoxon test. The statistical significance level was accepted as p<0,05. Results: A total of 48 people, 35 women (72.9%) and 13 men (27.1) were included in this study. The mean age is 22.2±2.7 and the median age is 22 ( min:19- max: 36). In the pre-test, 62.5% of the participants have inadequate /problematic health literacy level. In the post-test 41.7% of the participants have excellent level and 33.3% of the participants have sufficient level. Only 25% of the participants have insufficient problematic level. Conclusion: A range of skills and competencies such as accessing information, understanding, applying and critical thinking are required to protect and improve helath and to use health services correctly and effectively. The biggest factor that will ensure this is to improve health literacy levels. Good levels of the health literacy contribute to improving healt outcomes. At this point, it is of great importance to improve the health literacy levels of the society. In order to achieve this, it is necessary to improve the health literacy levels of all healthcare professionals who work in every step of the health service delivery to the community.